Investigating distinct semantic processing ability in individuals with dementia using the n-back task. Issue 2 (1st February 2022) - N., Hema; Devi, N.; Benoy, Jesnu Jose
ABSTRACT: Background: Assessment of working memory is fundamental in any evaluation of cognitive abilities. Working memory is crucial in the processing of any linguistic stimuli. Encoding, storing, and manipulating information in working memory are critical for perception as well as cognition. The decline in working memory has been reported in normal as well as pathological aging. Aims: The present study aimed to assess working memory capacity using a paradigm within E-Prime software and study its effect on linguistic processing ability in adults with and without dementia using the n-back task. Methods and Procedures: A standard group comparison was carried out across 10 neurotypical individuals and 7 individuals with dementia. A working memory task (n-back) was employed and the effect of various semantic stimuli categories on working memory was identified. Outcome and Results: The findings of this study revealed that individuals with dementia significantly differ in their working memory capacity when compared to neurotypical individuals. Poor working memory capacity could be due to the impaired ability to access semantic information of their linguistic ability and slow processing speed. Differences were also found concerning the processing of various semantic stimuli categories within both the study groups. Increased reaction time with poor working memory threshold was observed objectively in individuals with dementia compared to neruotypicals. The differences in terms of reaction time are attributed to the varied processing load put forth by different semantic stimuli within the working memory and to some extrinsic factors such as familiarity with the stimulus. Conclusions: The study evidences the importance of objective working memory assessment in differentiating individuals with dementia and neurotypical individuals.